PERLINDUNGAN HUKUM TERHADAP PERKAWINAN TIDAK TERCATAT DALAM ADMINISTRASI KARTU KELUARGA DI INDONESIA - Umilia Zakiatuz Zahro Umilia; Bashori Alwi (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Marriage registration is a crucial legal mechanism to ensure legal certainty and protection for Indonesian citizens as mandated by Law Number 1 of 1974. However, in practice, unregistered marriages remain widespread due to social and economic factors, leading to legal problems particularly for wives and children concerning rights to maintenance, inheritance, and population documents. This study aims to analyze the urgency of marriage registration and evaluate the policy of including the "Unregistered Marriage" status on the Family Card as regulated by the Minister of Home Affairs Regulation Number 108 of 2019. Using a normative juridical method with a literature review approach, this research identifies between administrative policies that facilitate the inclusion of unregistered marriage status through a Statement of Absolute Responsibility (SPTJM) on one hand, while on the other hand, such policies have not yet guaranteed substantive legal protection for women and children. Critical analysis of the normative disharmony between the administrative convenience offered by Minister of Home Affairs Regulation Number 108 of 2019 and the principle of legal certainty in the Marriage Law, as well as its impact on long-term protection for wives and children. The findings reveal that although this policy facilitates access to public services administratively, the research implications emphasize the need for more comprehensive regulatory reinforcement so that legal protection is not merely administrative in nature.